1979
DOI: 10.1002/bjs.1800661203
|View full text |Cite
|
Sign up to set email alerts
|

A comparative randomized trial of heparin versus streptokinase in the treatment of acute proximal venous thrombosis: An interim report of a prospective trial

Abstract: A controlled, prospective study comparing streptokinase and heparin treatment has been completed in 51 patients presenting with acute proximal venous thrombosis of less than 8 days' clinical duration. Patients were studied by means of pre-treatment, post-treatment, 3- and 12-monthly phlebography and pulmonary perfusion scanning and were followed up at 3-monthly intervals. Of the 26 patients randomized to receive streptokinase, therapy was stopped in 3 because of complications. Phlebography 5 days after startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
1
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(84 citation statements)
references
References 13 publications
0
81
1
2
Order By: Relevance
“…Although several studies have compared systemically delivered thrombolytics with anticoagulation alone for DVT, few evaluated the occurrence of PTS as a primary outcome. [93][94][95][96] Although this limited number of studies suggested a reduction in PTS, the risk of major bleeding was greater with systemic thrombolysis than with anticoagulation alone or CDT. 96,97 Moreover, there is a nontrivial failure rate of systemic thrombolysis resulting, in part, from the poor concentration and penetration of thrombolytics within the thrombus itself.…”
Section: Thrombolysis/endovascular Therapies To Prevent Ptsmentioning
confidence: 99%
“…Although several studies have compared systemically delivered thrombolytics with anticoagulation alone for DVT, few evaluated the occurrence of PTS as a primary outcome. [93][94][95][96] Although this limited number of studies suggested a reduction in PTS, the risk of major bleeding was greater with systemic thrombolysis than with anticoagulation alone or CDT. 96,97 Moreover, there is a nontrivial failure rate of systemic thrombolysis resulting, in part, from the poor concentration and penetration of thrombolytics within the thrombus itself.…”
Section: Thrombolysis/endovascular Therapies To Prevent Ptsmentioning
confidence: 99%
“…Thrombolytic therapy for proximal thrombosis does produce thrombolysis and at follow-up prevents the development of postphlebitic limb (Amesen et at. 1978at. , Elliot et at.…”
Section: Discussionmentioning
confidence: 99%
“…17 Two follow-up studies subsequently observed that PTS developed less frequently in patients treated with streptokinase compared with heparin alone at long-term follow-up, but these studies were small and did not use validated outcome measures of PTS. 18,19 In addition, bleeding complications were frequent (14% vs 4% in a pooled analysis) in the patients treated with streptokinase. 17 For this reason, systemic streptokinase infusions are not used for DVT treatment in current practice.…”
Section: Systemic Thrombolytic Therapymentioning
confidence: 98%